What historical moments are highlighted by university professors and researchers when reconstructing their professional and academic trajectories in Argentina during the period 1976-2007? (Papeles, 2024)
This article arises from the results obtained within the framework of the PISAC CTI 2024 project, entitled “Territorial asymmetries in Science, Technology and Innovation: Federal and inter-institutional networks for the evaluation of proposals and possible itineraries in current Argentina”, directed by Victor Hugo Algañaraz Soria. The central objective of this project was to explore the existing disparities in the processes of production and circulation of knowledge in different regions of Argentina, focusing on how public policies have influenced the development and consolidation of scientific and academic networks at the federal level.In this context, the present work recovers the words of nine university professors and researchers from different generations, various disciplines and different geographical areas, who when analyzing their professional and academic trajectories, relate difficulties or facilities for their development, with some state policies linked to Science. , Technology and Innovation (CTI) in Argentina. To do this, a temporary cut was made that covers 30 years: from the last coup d'état, in 1976, until 2007, with the end of Néstor Kirchner's government. From the data obtained, the dynamics of these policies are reconstructed and an attempt is made to understand the way in which they stimulated or hindered the development of the national scientific system and the careers of agents in the field.
Keywords: Science, Technology and Innovation; university professors and researchers; Argentina; professional trajectories; academic trajectories